Machining Parameters And Tool Geometry Optimization For Trimming Composite Laminates Using Response Surface Methodology - Sundi, Syahrul Azwan (2021)
In recent years, carbon fiber-reinforced polymer (CFRP) materials have gained tremendous attention from industries, especially in the aerospace industry due to their properties such as high strength-to-weight ratio and high corrosion resistance. In general, composite materials are usually manufactured in a near-net shape. Hence, secondary processes such as trimming, drilling and countersinking are usually applied to obtain the final desired dimension. Composite behavior such as its inhomogeneity, anisotropy, and interaction with the cutting tool becomes challenging for the manufacturers. Matrix cracking, un-cut fibers, fibers pullout, and burned matrices are the typical problems or damages that arise during the machining process which may contribute to the rejection of parts. Moreover, the abrasive nature of the reinforcement fibers of the composite materials induces rapid wear rate to the cutting tool during machining which finally impacted the overall manufacturing cost. Therefore, this present study aims to determine an optimum tool geometry for a router tool-type (the number of teeth and the helix angles) and the optimized machining parameters in minimizing workpiece damages during the trimming of CFRP material. The trimming performances evaluated include the trimmed surface roughness in the longitudinal and transverse direction as well as the cutting force. Surface roughness evaluation was done by utilizing the portable surface roughness while cutting force was measured using the piezoelectric-dynamometer. Besides, further qualitative observation on the trimmed surface quality, and the effect on the tool wear, were performed using an optical microscope and a 3-Dimensional (3D) surface topography imager. The design of experiment (DOE-Taguchi and Response Surface Method-RSM) is the primary method deployed in the overall research’s milestones. Through the statistical analysis, the machining parameters (cutting speed, Vc, and feed per tooth, fz) resulted in a more significant effect on the surface roughness and the cutting force value than the selected tool geometry. On the other hand, considering only the tool geometry, the most predominant factor that affected the trimmed surface quality was the number of teeth on the left side, followed by the helix angle and the number of teeth on the right side. The relationship for each mentioned response, namely, the surface roughness (in the longitudinal and transverse direction) and the cutting force associated with the tool geometry, was successfully established using statistical model analysis. The optimum tool geometry (the combination of the number of teeth on the left and the right side respectively; 12, 8 and the helix angle; 24○) and the machining parameters (the cutting speed, Vc118.47 m/min and the feed per tooth, fz 0.05 mm/rev) were chosen based on the highest desirability score. The new optimum router tool geometry was fabricated and a validation experimental work was performed which finally confirmed its validity by obtaining the relative error between the predicted and the experimented data less than 10%. Ultimately, the main aim of the present study which was to determine an optimum tool geometry for a router tool-type geometry that can accommodate the trimming results, namely minimum surface roughness (the longitudinal and transverse direction), the cutting force and the tool wear has been successfully achieved.